«Wrong fish» or wrong hypotheses: what happens to nekton of the Pacific waters at Kuril Islands? - V. P. Shuntov; O. A. Ivanov (Известия ТИНРО)
A phenomenon of undulating fluctuations of nekton abundance in the Kuroshio system is discussed on example of japanese sardine Sardinops melanostictus, as the most abundant and the most fluctuating species. The so-called «sardine epochs» are distinguished according to this species abundance. The last such epoch ended in the early 1990s. Since 2014, structural changes occurred again in the nekton communities of the Pacific waters off Kuril Islands, caused by expansion of southern fish and squid species, primarily japanese sardine and chub mackerel Scomber japonicus, and decreasing in abundance of japanese anchovy Engraulis japonicus and saury Cololabis saira. The scope of these changes allowed Russian fishermen to resume the fishery on japanese sardine and chub mackerel in the Russian exclusive economic zone since 2016. Annual catch of Japanese sardine increased steadily from 6,700 t in 2016 to 315,500 t in 2020. Over these 5 years, Russian fishermen landed 531,700 t of sardine and 167,900 t of chub mackerel. However, many Russian fishery forecasters believe that these reconstructions is only a «rehearsal» of the upcoming «sardine epoch», being based on formal climatic indices, without delving into the mechanisms of abundance fluctuations. The authors note that new «sardine epochs» cannot be predicted as completely similar to the previous ones. Several hypotheses on causes of the beginning and end of japanese sardine blooms are considered critically, and the conclusion is made that mechanisms which determine its year-classes strength are still unclear, as well as the reasons of undulating fluctuations of this species and some other nekton species abundance, because of high complexity of this problem.